A survey of wild marine fish identifies a potential origin of an outbreak of viral haemorrhagic septicaemia in wrasse, Labridae, used as cleaner fish on marine Atlantic salmon, Salmo salar L., farms. Issue 6 (8th August 2014) - Wallace, I S; Donald, K; Munro, L A; Murray, W; Pert, C C; Stagg, H; Hall, M; Bain, N
Abstract Viral haemorrhagic septicaemia virus (VHSV) was isolated from five species of wrasse (Labridae) used as biological controls for parasitic sea lice predominantly, Lepeophtheirus salmonis (Krøyer, 1837), on marine Atlantic salmon, Salmo salar L., farms in Shetland. As part of the epidemiological investigation, 1400 wild marine fish were caught and screened in pools of 10 for VHSV using virus isolation. Eleven pools (8%) were confirmed VHSV positive from: grey gurnard, Eutrigla gurnardus L.; Atlantic herring, Clupea harengus L.; Norway pout, Trisopterus esmarkii (Nilsson); plaice, Pleuronectes platessa L.; sprat, Sprattus sprattus L. and whiting, Merlangius merlangus L. The isolation of VHSV from grey gurnard is the first documented report in this species. Nucleic acid sequencing of the partial nucleocapsid (N) and glycoprotein (G) genes was carried out for viral characterization. Sequence analysis confirmed that all wild isolates were genotype III the same as the wrasse and there was a close genetic similarity between the isolates from wild fish and wrasse on the farms. Infection from these local wild marine fish is the most likely source of VHSV isolated from wrasse on the fish farms.